OPPORTUNITIES OF RUSSIAN ADOPTED MILK FORMULA WITH PARTIALLY HYDROLYZED PROTEIN IN NUTRITION OF INFANTS - O.L. Lukoyanova; T.E. Borovik; N.G. Zvonkova; N.N. Semenova; V.A. Skvortsova ("Paediatrician" Publishers LLC, 2011)
The article presents modern data on the formula of breast milk and principles of adaptation of children's milk mixtures. Authors show the reasonability of inclusion of some ingredients in the mixtures. The proper experience of nutrition with children's milk formula «Agusha Gold 1» is presented, its influence on physical development of infants first 6 months old is analyzed. The product is welltolerated with children without allergic family history and with infants from risk groups of atopy and ones with minimal allergic symptoms (not related to cow milk proteins). Most children with mild and changeable allergic symptoms showed total absence of dry skin on cheeks and rash. Key words: breast milk, breast feeding, children's milk formulas, bifidobacteria, oligosaccharides, allergy prophylaxis. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 93-99)